Exploring the drivers of digital technology adoption for enhancing domestic tax mobilization in Ghana - Alexander Asmah; Kingsley Ofosu Ampong; Dzifa Bibi; Wihlemina Ofori (International Journal of Information Management Data Insights)
Purpose: This study investigates the determinants of tax compliance through the lens of performance expectancy, effort expectancy, social influence, facilitating conditions and hedonic motivation. Design/methodology/approach: The study adopted both quantitative and qualitative research methods to gather data on the adoption of tax technologies. Based on the five determinants, a conceptual framework was developed consisting of seven proposed hypotheses tested through a structural equation model. Interviews were conducted to gain further insight into the drivers of the taxpayers’ portal in Ghana. Findings: The study finds that performance expectancy and effort expectancy are the most significant factors predicting tax compliance intentions, indicating that taxpayers consider the portal as a useful tool in managing their taxes and very easy to use. It reduces their exposure to corrupt government officials and lessens their cost of paying taxes. It is also very convenient and serves as a useful way to avoid the long queues they experience at the tax offices. The study recommends that the Ghana Revenue Authority (GRA) and the Ministry of Finance (MoF) should promote more revenue collection technologies and create more awareness among taxpayers to utilise the portal. Originality/value: The taxpayers’ portal in Ghana was recently introduced to enhance revenue mobilisation. No empirical research has been conducted to identify the adoption factors which will aid its smooth implementation. This paper thus provides significant value to both literature and practice.